MEG-guided analysis of 7T-MRI in patients with epilepsy. (August 2018) - Colon, A.J.; Osch, M.J.P. van; Buijs, M.; Grond, J.v.d.; Hillebrand, A.; Schijns, O.; Wagner, G.J.; Ossenblok, P.; Hofman, P.; Buchem, M.A.v.; Boon, P.
Highlights: Finding abnormalities on MRI predicts successful epilepsy surgery. In 3T MRI negative focal epilepsy visual analysis of 7T MRI has added value. MEG guidance enhances the gain of visual inspection of 7T MRI. Abstract: Purpose: To study possible detection of structural abnormalities on 7T MRI that were not detected on 3T MRI and estimate the added value of MEG-guidance. For abnormalities found, analysis of convergence between clinical, MEG and 7T MRI localization of suspected epileptogenic foci. Methods: In adult patients with well-documented localization-related epilepsy in whom a previous 3T MRI did not demonstrate an epileptogenic lesion but MEG indicated a plausible epileptogenic focus, 7T MRI was performed. Based on semiologic data, visual analysis of the 7T images was performed as well as based on prior MEG results. Correlation with other data from the patient charts, for as far as these were available, was analysed. To establish the level of concordance between the three observers the generalized or Fleiss kappa was calculated. Results: In 3/19 patients abnormalities that, based on semiology, could plausibly represent an epileptogenic lesion were detected using 7T MRI. In an additional 3/19 an abnormality was detected after MEG-guidance. However, in these later cases there was no concordance among the three observers with regard to the presence of a structural abnormality. In one of these three cases intracranial recording was performed, proving the possible abnormality on 7T MRI to be the epileptogenic focus. Conclusions: In 32% of patients 7T MRI showed abnormalities that could indicate an epileptogenic lesion whereas previous 3T MRI did not, especially when visual inspection was guided by the presence of focal interictal MEG abnormalities.